Study the Effect of Ceylon Cinnamon (Cinnamomum Zeylanicum) Powder on Some Physiological Parameters in Broiler Chicks - Sura Safi Obayes Khafaji (Journal of Global Pharma Technology, 2018)
The current study aimed to investigate the effects that could be caused by ceylon cinnamon (Cinnamomum zeylanicum) powder addition to diet of broileron some physiological parameters. A total of 150 one-day-old mixed-sex broiler chicks were distributed into 3 treatments, comprising 5 replicates per treatment, with 10 chicks for each replicate. 1st group (control) fed on the standard diet during the experimental period (42 days), 2nd group (T1) and 3rd group (T2) fed on standard diet mixed with 500&1000 mg/kg of CNP, respectively. On 1st and 42nd day of experiment, body weight was recorded. As well as, blood samples were collected at the end of experiment, for assessment of RBC and WBC counts, PVC, Hemoglobin concentration (Hb) and heterophils/lymphocytes ratio (H/L). Total protein, Albumin, globulin, Triiodothyronine (T3) and Tetraiodothyronine (T4) concentrations in blood serum were determined. The statistical analysis registered the significant (P<0.05) elevation in the body weight on 42nd day of experiment inT1 and T2 groups comparing with the control. The results revealed that the second and third groups recorded significant (P<0.05) increase in RBC and WBC counts, as well as, PVC and HB concentration. While H/L significant (P<0.05) decline in T1 and T2 groups comparing with the control. At the same time, the result of total protein, globulin, T3 and T4concentrations revealed a significant increment (P<0.05) in two treated groups when compared with control. Therefore, it was concluded that the use of cinnamon powder can affected positively on some physiological traits and broiler performance.Key words: Cinnamon powder, Physiological parameters, Broiler chicks.